LOCAL IMMUNITY AND GUT MICROFLORA IN THE SALMONELLA CARRIERS АND APPROACHES TO ITS TREATMENT - I. N. Chainikova; A. I. Smoliagin; M. V. Skachkov; T. N. Kalinina; O. V. Bukharin (Медицинская иммунология, 2014)
Abstract. Features of local immunity were studied in the patients with Salmonella infection at reconvalescence, both without carriership, and in reconvalescent carriers of microbial flora (RCM). In RCMs, as compared to non-carriers, some alterations in gut microbiocenosis were revealed, along with local deficiency of antimicrobial defense factors, i.e., lactoferrin, lysozyme, secretory IgA, free secretory component, antibodies to Salmonella O-antigen, IgA, as opposed to high levels of IgM, IgG (due to IgG1 and IgG4), cytokines (IL-6, IL-8, IFNγ, IL-4). It was shown that sIgA and IgA deficiency are connected with their mangling local production, whereas the revealed increase in IgМ and IgG concentrations proved to be a consequence of increased local synthesis. Application of polyoxidonium (PO) in RCMs lead to improvement in the gut microenvironment, thus reflected by decreased contamination with facultative flora, disappearance of Proteus, Candida spp. and recovery of indigenous anaerobic flora in 92 per cent of cases. Positive dynamics of local immunity associated with PO treatment was justified by restoration of total IgA and sIgA concentrations, due to enhanced local synthesis, increase in free secretory component, higher titers of antibodies to Salmonella O-antigen, and changes in cytokine contents, with restoration of Th1/Th2 cytokine balance. Under in vitro conditions, a PO-associated suppression of anti-complement Salmonella activity was registered, thus rendering positive effects of the drug towards symbionts in the «host-parasite» system, and shortening the terms of microbial excretion in Salmonella carriers.